Mathematical modeling of steady MHD Casson fluid flow with stretching porous walls in existence of radiation, chemical reaction, and thermal diffusion effect. (16th September 2021) - Jangid, Sanju; Mehta, Ruchika; Mehta, Tripti; Sushila,
Abstract : This expression presents the steady (independent of time) MagnetoHydroDynamics (MHD) Casson fluid (non‐Newtonian shear‐thinning) flow with thermal radiative impression between two equivalent plates within stretched porous walls. The mass and heat transfer experimentation founded in the company of buoyancy force, viscous dissipative impact, and thermo diffusion impact on squeezing flow are explained along with thermal radiative impression also with heat source/sink outcomes. The governing PDEs (partial differential equations) modified into ODEs (ordinary differential equations) via appropriate similarity modification. The ODEs are extricated by Runge–Kutta's fourth‐order scheme and shooting performance. The outcomes of several parameters (nondimensional numbers) on velocity, temperature, and concentration are evaluated with the service of diagrams and tables. The result displays that the fluid velocity growths with increment of Grashof number. The effect of Reynolds number, Hartman number (magnetic number), non‐Newtonian Casson fluid parameter, and so forth are also interpreted for velocity profile, mass transfer, and heat transfer. In the last, the skin friction coefficient, Sherwood number (mass transfer coefficient), and Nusselt numbers (heat transfer coefficient) are also reputed. Also, validation of the current paper is given in Table 2.